2011
DOI: 10.1111/j.1365-2109.2011.02845.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein requirement of juvenile shi drum, Umbrina cirrosa (L.)

Abstract: This study was undertaken to determine the dietary protein requirement of shi drum (Umbrina cirrosa L.) with an initial weight of 86.3 AE 0.4 g. The ¢sh were fed ¢ve isoenergetic diets containing dietary protein levels ranging from 35% to 59% by 6% increments [the estimated digestible protein (DP) levels ranged between 29.6% and 52.8%], and the growth response over a 10-week period was monitored. Each experimental diet was given to triplicate groups of ¢sh. The ¢nal weight, weight gain and daily growth coe⁄cie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
9
17
1
Order By: Relevance
“…Similarly, ash content, moisture, crude energy, and fillet lipids were not affected by changes in dietary protein levels. This is also consistent with other studies in some fish species (Monentcham, Pouomogne, & Kestemont, 2010;Akpinar, Sevgili, Ozgen, Demir, & Emre, 2012). Dry matter and CP values were similar to those found in pirarucu juvenile fillets of 7-16 kg by Fogaça et al (2011).…”
Section: Resultssupporting
confidence: 81%
“…Similarly, ash content, moisture, crude energy, and fillet lipids were not affected by changes in dietary protein levels. This is also consistent with other studies in some fish species (Monentcham, Pouomogne, & Kestemont, 2010;Akpinar, Sevgili, Ozgen, Demir, & Emre, 2012). Dry matter and CP values were similar to those found in pirarucu juvenile fillets of 7-16 kg by Fogaça et al (2011).…”
Section: Resultssupporting
confidence: 81%
“…Mean values (± SEM) of the nutritional parameters from the 16L:8D group of the present study. Our results are compared with the results found in shi drum by Segato et al (2006Segato et al ( , 2007 (mean values ± SD) and Zafer et al (2012) 16L:8D group (dorsal and ventral fillet) Dorsal fillet (Segato et al, 2007) Whole-body (Segato el al., 2006) Whole -body (Zafer et al, 2012 Imsland et al (2013) studied the long-term effect of photoperiod manipulation for 46 months and found that the shortterm exposure to 24L stimulated growth, whereas the long-term rearing at 24L reduced growth. Thus, at harvest, the greatest mean weights were reached in the group previously kept to short-term exposure at 24L and then transferred to 16L:8D until harvest.…”
Section: Discussionmentioning
confidence: 89%
“…Excess protein in the diet increases the production cost and can lead to pollution of pond environment. Therefore, it is necessary to optimise the protein levels in the fish diets considering economics and environmental perspective (Siddiqui and Khan, 2009;Akpinar et al, 2012).…”
mentioning
confidence: 99%